CareLoc: Uma Aplicação de Localização de Pacientes usando Beacons em Ambiente Domiciliar - Rodrigues, Matheus S.; Carvalho, Sérgio T. (Companion Proceedings of the Brazilian Symposium on Computing Applied to Healthcare (SBCAS); 2020: Companion Proceedings of the 20th Brazilian Symposium on Computing Applied to Healthcare, 2020)
One consequence of the increasing elderly population in Brazil and the demand for specific care with this age group is the creation of remote patient monitoring applications. This class of applications has the potential to monitor important patient care information in the home environment, such as physiological data and location. This paper describes the results of a survey conducted to identify existing indoor location methods and presents a mobile application designed to handle user position monitoring and establishment using Bluetooth Low Energy beacons (BLE).